Organothiol Monolayer Formation Directly on Muscovite Mica. (18th December 2019) - de Poel, Wester; Brugman, Sander J. T.; van de Ven, Kim H. A.; Gasseling, Anouk; de Lange, Jordi; Townsend, Eleanor R.; Engwerda, Anthonius H. J.; Jankowski, Maciej; Blijlevens, Melian A. R.; Werkhoven, Ben L.; Drnec, Jakub; Carlà, Francesco; et al.
Abstract: Organothiol monolayers on metal substrates (Au, Ag, Cu) and their use in a wide variety of applications have been extensively studied. Here, the growth of layers of organothiols directly onto muscovite mica is demonstrated using a simple procedure. Atomic force microscopy, surface X‐ray diffraction, and vibrational sum‐frequency generation IR spectroscopy studies revealed that organothiols with various functional endgroups could be self‐assembled into (water) stable and adaptable ultra‐flat organothiol monolayers over homogenous areas as large as 1 cm 2 . The strength of the mica–organothiol interactions could be tuned by exchanging the potassium surface ions for copper ions. Several of these organothiol monolayers were subsequently used as a template for calcite growth. Abstract : Schichtbetrieb : Organothiole mit verschiedenen funktionellen Endgruppen können auf Muskovit zu (wasser)stabilen, anpassungsfähigen, ultraflachen Organothiol‐Monolagen über homogene Flächen von bis zu 1 cm 2 angeordnet werden. Die Stärke der Muskovit‐Organothiol‐Wechselwirkung kann durch den Austausch von Kalium‐Oberflächenionen gegen Kupfer‐Ionen geregelt werden.